Linguistic analysis of morphological aspects in English - Turaeva Zukhra (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Morphological analysis is the study of the structure and formation of words through examining their components, known as morphemes. This approach helps to understand how different morphemes combine to create new words, convey meaning, and indicate grammatical relationships. It encompasses various aspects like how new words are formed from existing ones, how variations in form occur, and how to classify morphemes as either free or bound. In this article, morphological aspects are conveyed with the linguistic perspectives by different scholars.